Relationship between pathogenic factors and the prevalence of temporomandibular joint dysfunctions in children - Rosa Ibragimova; Gulzhan Yermukhanova; Assilbek Yessirkepov; Gulzakira Xetayeva; Zhamilya Yerkibayeva (Elsevier, 2023)
Purpose: The purpose of the research is to study the relationship between the certain pathogenic factors and the prevalence of functional disorders of TMJ in children and adolescents with mental development delay (MDD), in practically healthy persons of similar age living in children's homes and in a family. Methods: The study was carried out using the method of observation, systematization, analysis and synthesis of the results obtained in the course of laboratory experiments. Results: Symptoms of TMD include decreased mandibular range of motion, muscle and joint pain, joint crepitus, and functional limitation or deviation of jaw opening. The mentioned symptoms were revealed in 40.1% of children and adolescents with MDD, less frequently in 32.62% of children and adolescents living in children's homes, and in 35.32% of practically healthy persons living in families and their rate increased with ageing. More often it was revealed in girls. Conclusions: According to the results of the study, the authors found that children and adolescents with MDD, symptoms of TMJ dysfunctions occur more often and begin at an earlier age than in practically healthy ones.